2020
DOI: 10.2147/cmar.s245622
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic Value of Inflammation Biomarkers for Survival of Patients with Neuroblastoma</p>

Abstract: The prognostic significance of inflammation-based biomarkers for neuroblastoma (NB) has not been investigated before. The aim of this study was to evaluate the prognostic value of pre-treatment inflammation biomarkers in children patients with NB. Patients and Methods: Patients diagnosed with NB from 2008 to 2016 in our institution were enrolled in this study. The clinical data and survival outcomes were retrospectively reviewed. Inflammation biomarkers or scores including C-reactive protein (CRP), albumin (AL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 67 publications
3
31
2
Order By: Relevance
“…Although some studies have suggested that the tumor site was related to the prognosis of NB (16, 17), we did not observe an association between tumor site and survival time in this analysis. Tumor size was identified as an independent predictor of OS and CSS, corroborating evidence reported by recent studies (17,18). However, Zhou et al (19) found that tumor size did not exert a significant prognostic effect on the rate of event-free survival.…”
Section: Discussionsupporting
confidence: 81%
“…Although some studies have suggested that the tumor site was related to the prognosis of NB (16, 17), we did not observe an association between tumor site and survival time in this analysis. Tumor size was identified as an independent predictor of OS and CSS, corroborating evidence reported by recent studies (17,18). However, Zhou et al (19) found that tumor size did not exert a significant prognostic effect on the rate of event-free survival.…”
Section: Discussionsupporting
confidence: 81%
“…CRP >10 mg/L and albumin <3.5 mg/dl receive one point each, and the score classifies the patients into three total scores of 0, 1, or 2. mGPS does not allocate a score to hypoalbuminemia without a rise in CRP to above 10 mg/L. hs-mGPS provides a similar classification to mGPS with a lower CRP threshold (>3 mg/L) (94,95). These markers also have proven roles in predicting various cancers (94,95).…”
Section: Glasgow Prognostic Score Modified Gps and High-sensitivity Mgpsmentioning
confidence: 99%
“…Previous studies have reported the prognostic values of hs-mGPS, hsCRP/ALB, and PNI in cancers, 14–18 , 27 which were derived from two indicators of hsCRP, LYM, and ALB. To maximize the prognostic performance of these indicators, we combined hsCRP, LYM, and ALB for the first time to construct a new prognostic score, IINS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the prognostic values of hs-mGPS, hsCRP/ALB, and PNI in cancers, [14][15][16][17][18]27 which were derived from two indicators of hsCRP, LYM, and ALB. To maximize the prognostic performance of these [30][31][32] our study revealed the AUCs of 0.591, 0.604 and 0.656 for hs-mGPS, hsCRP/ALB and PNI, which implies the repeatability of our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation